المشهور المبني على ضعيف: دراسة تأصيلية تطبيقية - كتاب الطهارة أنموذجا - باهي, ياسين (جامعة الوادي - University of Eloued, 2021)
يكثر في كتب متأخري المالكية استعمال عدد من المصطلحات كالمشهور والظاهر والضعيف والراجح والشاذ، كما ظهر عند هؤلاء الأئمة عبارة تداولوها في كتبهم هي: "المشهور المبني على ضعيف"، وإني في هذا البحث سأبيّن المقصود من هاته العبارة ببيان أفرادها وما له صلة بها، ثم ببيان المقصود منها، كما سأحلّل وأناقش التعليل بهاته العبارة في مسائل فقهية في كتاب الطهارة، وقد سعيت ألا يفوتني شيء منها. توصلت في هذا البحث من خلال الجزء التطبيقي إلى عدد من النتائج أهمها: - الحكم على الأصل بالضعف غير مقبول في كثير من الأحيان؛ إذ إنّه قد يكون أحد المشهورين وليس ضعيفا. - تعليل القول بأنه من باب المشهور المبني على ضعيف لم يسلِّم به ولم يرتضه حذّاق المذهب في كثير من الأحيان، إمّا بالإعراض عن ذكره، أو بالردّ عليه. - العدول في الفرع عن البناء على المشهور في الأصل أحيانا يكون سببه مراعاة الخلاف القويّ في الأصل، أو إعمال مبدأ التحوّط وسدّ الذريعة، أو قاعدة اليسير المعفوّ عنه أو غيرها من القواعد والأصول. - المحافظة على استقرار بناءِ الفروع على الأصول أولى من التعليل بالعبارة محلّ الدراسة. A number of terms are used frequently in the books of late Maliki scholars, such as the famous, the apparent, the weak, the more correct and the odd one, as it appeared among these imams a phrase that they used in their books, which is: "the well-known based on the weak." In this paper, I will explain what is meant by this phrase by explaining its individuals and what is related to it, then by explaining what is meant by a composite, and I will also analyze and discuss the reasoning with this phrase in jurisprudential issues in the provisions of chapter of purity, and I have tried not to miss anything of it. In this research, I concluded through the practical part a set of results, the most important of which are: - Judging the asset as weak is often not acceptable; As it may be one of the two famous sayings and not a weak one. - Explanation of the saying that it is a matter of the well-known saying that is based on a weak saying that was not recognized and the imams of the doctrine did not accept it in many cases, either by refraining from mentioning it, or by responding to it. - Leaving the branch building according to the well-known saying in the original is sometimes due to taking into account the strong disagreement in the origin, or applying the principle of precaution and blocking the pretext, or the rule of the pardoned easy or other rules and principles. - The stability of the branches ’construction on the origins is more important than the reasoning for the phrase in question.
The Famous saying that is based on a weak saying: An applied Fundamental Study - Chapter of Purity as a Model -
مقال
Keywords: لمشهور ; الضعيف ; المشهور المبني على ضعيف ; كتاب الطهارة ; المذهب المالكي; The famous saying; weak saying; The famous saying based on a weak saying; Chapter of purity; The Maliki school of thought.